Dichotic Listening after Cerebral Hemispherectomy: Methodological and Theoretical Observations - de Bode, Stella (2007)
We examined two commonly used dichotic listening tests for measuring the degree of hemispheric specialization for language in individuals who had undergone cerebral hemispherectomy: the Consonant-Vowel (CV) nonsense syllables and the Fused Words (FW) tests, using the common laterality indices f and λ. Hemispherectomy on either side resulted in a massive contralateral ear advantage, demonstrating nearly complete ipsilateral suppression of the left ear in the right hemispherectomy group but slightly less complete suppression of the right ear in the left hemispherectomy group. The results are consistent with the anatomical model of the ear advantage (Kimura, 1961). Most syllables or words are reported for the ear contralateral to the remaining hemisphere, while few or none are reported for the ear ipsilateral to the remaining hemisphere. In the presence of competing inputs to the two ears, the stronger contralateral ear-hemisphere connection dominates/suppresses the weaker ipsilateral ear-hemisphere connection. The λ index was similar in the two tests but the index f was higher in the CV than the FW test. Both indices of the CV test were sensitive to side of resection, higher in the right hemispherectomy than in the left hemispherectomy groups.